European research priorities for intracerebral haemorrhage - Steiner, Thorsten; Petersson, Jesper; Salman, Rustam Al-Shahi; Christensen, Hanne; Cordonnier, Charlotte; Csiba, Laszlo; Harnof, Sagi; Krieger, Derk; Mendelow, David; Molina, Carlos; Montaner, Joan; Overgaard, Karsten; et al. (Cerebrovascular diseases, 2011)
Over 2 million people are affected by intracerebral haemorrhage (ICH) worldwide every year, one third of them dying within 1 month, and many survivors being left with permanent disability. Unlike most other stroke types, the incidence, morbidity and mortality of ICH have not declined over time. No standardised diagnostic workup for the detection of the various underlying causes of ICH currently exists, and the evidence for medical or surgical therapeutic interventions remains limited. A dedicated European research programme for ICH is needed to identify ways to reduce the burden of ICH-related death and disability. The European Research Network on Intracerebral Haemorrhage EURONICH is a multidisciplinary academic research collaboration that has been established to define current research priorities and to conduct large clinical studies on all aspects of ICH.
Gesehen am 21.10.2022